Effects of twin pregnancy and periconceptional undernutrition on maternal metabolism, fetal growth and glucose–insulin axis function in ovine pregnancy - Rumball, C W H (Blackwell Science Inc, 2008)
Although twins have lower birthweights than singletons, they may not experience the increased disease risk in adulthood reportedly associated with low birthweight. In contrast, another periconceptional event, maternal undernutrition, does not reduce birthweight but does affect fetal and postnatal physiology in sheep. We therefore studied maternal and fetal metabolism, growth and glucose–insulin axis function in late gestation in twin and singleton sheep pregnancies, either undernourished from 60 days before until 30 days after conception or fed ad libitum. We found that twin-bearing ewes had decreased maternal food intake in late gestation and lower maternal and fetal plasma glucose and insulin levels. Twin fetuses had fewer everted placentomes, grew slower in late gestation, and had a greater insulin response to a glucose challenge, but lesser response to arginine. In contrast, periconceptional undernutrition led to increased maternal food intake and a more rapid fall in maternal glucose levels in response to fasting. Periconceptional undernutrition increased the number of everted placentomes, and abolished the difference in insulin responses to glucose between twins and singletons. Thus, the physiology of twin pregnancy is quite different from that of singleton pregnancy, and is probably determined by a combination of factors acting in both early and late gestation. The inconsistency of the relationships between low birthweight and postnatal disease risk of twins may lie in their very different fetal development. These data suggest that twin pregnancy may be another paradigm of developmental programming, and indicate that twins and singletons must be examined separately in any study of fetal or postnatal physiology.